Synthesis of phosphonate and phostone analogues of ribose-1-phosphates - Nasomjai, Pitak; O'Hagan, David; Slawin, Alexandra M. Z. (Beilstein Journal of Organic Chemistry, 2009)
The synthesis of phosphonate analogues of ribose-1-phosphate and 5-fluoro-5-deoxyribose-1-phosphate is described. Preparations of both the α- and β-phosphonate anomers are reported for the ribose and 5-fluoro-5-deoxyribose series and a synthesis of the corresponding cyclic phostones of each α-ribose is also reported. These compounds have been prepared as tools to probe the details of fluorometabolism in S. cattleya.
Keywords: 5-fluoro-5-deoxyribose-1-phosphate; fluorometabolite biosynthesis; phosphonates; phostone; ribose-1-phosphate

(untitled) - Sanada, M.; Miyano, T.; Iwadare, S.; Williamson, J. M.; Arison, B. H.; Smith, J. L.; Douglas, A. W.; Liesch, J. M.; Inamine, E. (J. Antibiot., 1986)

(untitled) - Deng, H.; Cross, S. M.; McGlinchey, R. P.; Hamilton, J.; O'Hagan, D. (Chem. Biol., 2008)

(untitled) - O'Hagan, D.; Schaffrath, C.; Cobb, S. L.; Hamilton, J. T. G.; Murphy, C. D. (Nature, 2002)

(untitled) - Meyer, R. L.; Stone, T. E.; Jesthi, P. K. (J. Med. Chem., 1984)

(untitled) - Kandil, A. A.; Slessor, K. N. (J. Org. Chem., 1985)

(untitled) - Lal, G. S.; Pez, G. P.; Pesaresi, R. J.; Prozonic, F. M. (Chem. Commun., 1999)

(untitled) - Fox, D. T.; Poulter, C. D. (J. Org. Chem., 2005)

(untitled) - Baker, S. J.; Young, D. W. (J. Labelled Compd. Radiopharm., 2000)

(untitled) - Kohli, V.; Blöcker, H.; Köster, H. (Tetrahedron Lett., 1980)

(untitled) - Shimuzu, M.; Nakahara, Y.; Yoshioka, H. (Tetrahedron Lett., 1985)

(untitled) - Ashton, T. D.; Scammells, P. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - McClard, r W.; Witte, J. F. (Bioorg. Med. Chem. Lett., 1994)

(untitled) - Bosco, M.; Bisseret, P.; Eustache, J. (Tetrahedron Lett., 2003)